Introduction to string theory - Carlo Maccaferri, Fabio Marino, Beniamino Valsesia (SciPost Physics Lecture Notes)
These are lecture notes of the introductory String Theory course held by one of the authors for the master program of Theoretical Physics at Turin University. The world-sheet approach to String Theory is pedagogically introduced in the framework of the bosonic string and of the superstring.